The PREDICTS database : A global database of how local terrestrial biodiversity responds to human impacts - Hudson, Lawrence N. (2014)
Fil: Cerezo, Alexis. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Métodos Cuantitativos y Sistemas de Información. Buenos Aires, Argentina.